48V Vernier Machines in the Context of Future Concepts for Light eMobility - Lüddecke, Bernhardt; Thyroff, Dominik; Schönborn, Andreas; Hahn, Ingo (Aachen Colloquium, Automboile and Engine Technology, Band 2, 2019)
Year upon year more people live in urban areas, megacities and other spaces that suffer from ambient air pollution. Health and quality of living can be significantly reduced. This can even be a stronger driver for change than future legislation demands. Reshaping city traffic requires a new mix of transportation. Electric two-wheelers will find their spot, e.g. for the first or last mile of transportation or within sharing concepts. Adapting proven and mature automotive technology paves the way for this transition. 48V technology has gained a lot of attention in the automotive sector due to its potential to meet the rising demand for sophisticated electric support functions. Continental has already developed a wide variety of 48V automotive products, including belt starter-generators, high speed electric compressors, and a host of fluid management applications. Transferring this technology to the global non-automotive market is a promising opportunity. Propulsion systems for eScooters & eMopeds often comprise small high-speed machines, combined with a gear or a gearbox to adapt torque and speed. However, using gears involves several challenges like Noise, Vibration, Harshness (NVH), lubrication and increased weight. Due to the similarity of magnetic gears and permanent magnet machines, new direct drive concepts with magnetic gearing effect were investigated by several researchers with the goal to increase the torque of direct drives [1–3]. Among those machines, the ‘Vernier’-design offers a promising base for 48V high-torque-low-speed machines with an outstanding torque to volume ratio [1, 4]. This paper compares the performance of different Vernier machines with corresponding standard Permanent Magnet Synchronous Machine (PMSM) layouts. Those investigations are put into the context of future mobility concepts and their requirements. For instance, Continental’s Multi Modal Journey Strategy is outlined to optimize city traffic and travel time. Two-wheelers are part of this data driven service approach, leveraging the synergies of powertrain, cloud and connectivity solutions [5
Keywords: Vernier machine; 48V Systems; Light eMobility

Accurate Simulation of the Star Point Behavior of Inverter-fed Synchronous Motors using the measured Common Mode Impedance - Fritsch, Christoph; Hahn, Ingo (ECCE Europe 2024 - Energy Conversion Congress and Expo Europe, Proceedings, 2024)
Many insulation faults in industrial applications are caused by a too high voltage to ground at the star point of the motor. This applies especially for synchronous torque motors. The reason is a rather undamped resonance frequency of the star point voltage to ground which is mitigated by the inverter common mode voltages. The worst case leading to most of the failures is at standstill where all inverter phases produce the identical output voltage. It is useful to be able to simulate this star point voltage for this use case. If the star point of the motor is accessible the voltage transfer function can be measured to be able to simulate the behavior. But in almost any case the star point is not accessible. This paper shows how to determine the star point behavior by using only the measured frequency-dependent common mode impedance and how to simulate the behavior using a simple model.
CRIS-Team Scopus Importer:2025-02-04
Keywords: insulation; partial discharge; star point voltage; synchronous motor; Three-phase motor drive

A discrete elements model for ironless DC-machines with graphite brushes - Wagner, Johannes; Hahn, Ingo (20th International Conference on Electrical Machines and Systems, ICEMS 2017, 2017)
Keywords: DC-Machines; Commutation; Ironless Windings; Discrete-Elements-Model

Algorithm to List All Possibilities of Minimizing The Number of BSO’s of Matrix Converters - Igney, Jens; Hahn, Ingo (2024 Energy Conversion Congress & Expo Europe (ECCE Europe), 2024)
As with other self-commutated inverters, the matrix converter offers the option of discontinuous modulation. This paper presents an algorithm that lists all duty cycle matrices that allow pulse patterns with only six instead of twelve branch switching operations (BSO’s) per modulation period. It further provides a classification scheme for such duty cycle matrices. The algorithm can be used as a first step within improved modulation strategies with reduced number of branch switching operation
Keywords: AC-AC power conversion; matrix converters; pulse width modulation; branch switching operation (BSO); discontinuous modulation; classification scheme

Alternative ways of cooling an E-Core Flux-Switching Permanent Magnet Machine with Large Air-Gap - Lindner, Andreas; Hahn, Ingo (IECON 2016, 2016)
The work presents two alternative ways of cooling a flux-switching permanent magnet machine with a large air-gap length of 3 mm. The investigations are based on a small power machine (DSa = 100 mm, l = 80 mm) which is designed for the needs of a special application where a defined clearance between the stator and rotor is required to ensure the working principle. The increased air-gap volume promotes the machine cooling from the stator inner surface by means of applying ordinary rotor (step) skewing technique for the salient pole reluctance rotor. In order to proof this cooling concept a test-setup is build up for thermal evaluation purposes. A more widely applicable approach for the thermal heat dissipation within the machine stator is also presented. In this case, the heat is directly extracted from the coil sides of the stator phase winding employing heat pipes. This totally passive cooling technique can improve the efficiency of all kinds of machines by keeping the phase resistance at lower levels or alternatively allowing an increase of current density in the slot without the need of additional cooling equipment like a fan, a radiator or a liquid cooling circuit.
UnivIS-Import:2017-01-09:Pub.2016.tech.IE.LEEAS.altern

Analysis and improvement of a toroidal wound permanent magnet flux-switching machine - Lindner, Andreas; Hahn, Ingo (IEEE, 2015)
UnivIS-Import:2015-10-26:Pub.2015.tech.IE.LEEAS.analys

Analysis and Modelling of the Measurable, Electrical HF-Quantities of an IPMSM and their Dependencies - Hittinger, Christoph; Graus, Johannes; Hahn, Ingo; Wagner, Johannes (Electrical Machines and Systems (ICEMS), 2016 19th International Conference on, 2016)

Analysis of Flux Focusing Double Stator and Single Rotor Axial Flux Permanent Magnet Motor - Syed, Qurban Ali Shah; Hahn, Ingo (IEEE, 2016)
UnivIS-Import:2017-12-18:Pub.2016.tech.IE.LEEAS.analys

Analytical Time Domain Flux-MMF Model for the Flux Switching Machine - Kurtovic, Haris; Hahn, Ingo (2018 International Symposium on Power Electronics, Electrical Drives, Automation and Motion (SPEEDAM), 2018)
A modeling approach for the flux switching machine., based on the flux-MMF method is proposed. Under the model assumptions of radial flux and infinite iron permeability., the machine is simplified to current loadings and permeances along the air gap. These quantities are used to calculate the flux and induced voltage of the machine and are functions of the rotor angle and current phase. The modeling approach is independent of the machine type and is performed in the space and time domain., without transforming any quantities into the frequency domain. The results of the model are presented and a comparison to finite element results is give
Keywords: Flux Switching Machine; Modeling of Electrical Machines; Flux-MMF

Analytic power factor calculation for vernier machines with concentrated windings - Thyroff, Dominik; Hittinger, Christoph; Hahn, Ingo (2017 IEEE International Electric Machines and Drives Conference (IEMDC), 2017)
It is well-known that the power factor of Vernier machines is small compared to permanent magnet machines. However, the power factor equations already derived show a huge deviation to the finite-element analysis (FEA) when used for Vernier machines with concentrated windings. Therefore, this paper develops an analytic model to calculate the power factor of Vernier machines with concentrated windings and different numbers of flux modulating poles (FMPs) and stator slots. The established model bases on the winding function theory in combination with a magnetic equivalent circuit. Consequently, equations for the q-inductance and for the no-load back-EMF of the machine are derived, thus allowing the calculation of the power factor. Thereby, the model considers stator leakage effects, as they are crucial for a good power factor estimation. Comparing the results of the Vernier machine to those of a pm machine explains the decreased power factor of Vernier machines. In addition, a FEA confirms the results of the derived model.
Keywords: equivalent circuits; finite element analysis; machine windings; magnetic circuits; permanent magnet machines; power factor measurement; stators; FEA; Vernier machines; analytic model; analytic power factor calculation; back-EMF; concentrated windings; finite-element analysis; flux modulating poles; magnetic equivalent circuit; permanent magnet machines; power factor estimation; stator leakage effects; stator slots; winding function theory; Analytical models; Integrated circuit modeling; Mathematical model; Reactive power; Stator windings; Windings; Vernier machine; analytic model; concentrated windings; leakage; magnetic equivalent circuit; power factor

Analyzing the Estimation of Energy Consumption in the Trajectory Planning of an Industrial Robot - Hosseini, Sara; Hahn, Ingo (2024 IEEE 19th Conference on Industrial Electronics and Applications, ICIEA 2024, 2024)
This paper introduces a method for estimating the energy consumption during trajectory planning tasks for an industrial robot (IR) arm manipulator. The study focuses on modeling the electrical and mechanical losses of a 6-Degree of Freedom (DoF) robot arm manipulator from Universal Robots. Correspondingly, a power losses cost function (PLCF) is proposed to calculate the electromechanical energy losses. The objective is to estimate energy losses during trajectory planning in Cartesian space for a tool center point (TCP), starting from an initial point and ending at a final point. This is accomplished through an examination and analysis of the kinematics and dynamics, followed by measurement of velocity and acceleration terms for each motor at each joint of the UR3e robot arm in a laboratory setup. Since the gained results could be implemented on any other type of trajectory, in this work as a proof of results two circular trajectories with two different radii has been investigated. By the means of these two arbitrary trajectories, the impact of change of acceleration/deceleration and velocity of each PMSM motor on each 6 joints of the robot can be examined on the overall energy losses. The results provide estimations of energy loss changes throughout the trajectory of the robot manipulator and present the results of measured reduction terms.
CRIS-Team Scopus Importer:2025-02-04
Keywords: electromechanical losses; industrial robot; motion planning; power consumption; six degree of freedom robot

A New Approach in the Production of Electrical Motors Using Only Machining Processes - Hahn, Ingo; et al. (EDPC 2011, 2011)
As a new possibility of producing the electrical steel sheets of electrical motors, a motor sample was produced using just machining processes such as turning, drilling, milling and sawing. Therefore several strategies in the production flow were considered and tested. The idea behind this method of producing a motor is to avoid the expensive cutting processes and material deterioration. On the one hand punching, as the most common cutting method of electrical steel sheet, is only cheap for useful for high volume and not for samples or small series, on the other hand laser cutting, which is suitable for single production of motors, requires expensive tools. Moreover punching and laser cutting deteriorate the electrical steel sheets close to the cutting edges. Since machining processes can be adjusted in speed and cooled with a fluid, a less distinctive effect can be assumed. © 2011 IEEE.
UnivIS-Import:2015-04-16:Pub.2011.tech.IE.LEEAS.anewap
Keywords: Drilling; electrical steel sheets; machining process; turning

A New Method for the Estimation of the Influence of Stator Saturation on the Differential Inductances - Graus, Johannes; Hahn, Ingo (IEMDC 2013, 2013)
For sensorless position detection of permanent magnet synchronous machines at very low speed and standstill, signal injection methods are commonly used. As a prerequisite these so called saliency-tracking methods require a differential magnetic anisotropy of the machine, which is both position and load dependent and thus varying during operation. So the performance of sensorless operation strongly depends on the machine design. To investigate the influence of the stator saturation on the differential inductances of a machine with concentrated winding, a model based on a magnetic equivalent circuit is used. The results show that for some angles of the current vector the inductances do not vanish even for high currents. To explain this phenomenon a new method for the qualitative estimation of both the stator tooth and yoke saturation is derived that shows very good agreement with the simulation results. © 2013 IEEE.
UnivIS-Import:2015-04-16:Pub.2013.tech.IE.LEEAS.anewme
Keywords: concentrated winding; cross saturation; differential magnetic anisotropy; magnetic equivalent circuit; permanent magnet synchronous machine; sensorless position detection

A Performance Comparison of GaN FET and Silicon MOSFET - Khoshzaman, Shima; Hahn, Ingo (2021 22nd IEEE International Conference on Industrial Technology (ICIT), 2021)
Introducing the excellent advantages of using wide bandgap semiconductors such as gallium nitride (GaN) in the construction of the power devices has set a starting point for a new era in the history of power electronics. Replacing the silicon-based with GaN-based power devices promises a number of benefits. Higher power densities, switching speeds and temperature stabilities with lower on-state resistance, reduced conduction and switching losses and a reduction in the die size are some of the performance improvements that the GaN transistors offer. To show both the advantages and challenges regarding this new technology, the methodology for an eligible comparison between Si-based and GaN-based transistors has been explained. Experimental comparison has been performed between a 100 V commercially available enhancement mode GaN FET and two silicon-based MOSFETs, and the results are discussed in detai
Keywords: gallium nitride; silicon; wide bandgap devices; performance characterization

A simple method for the parameter identification of the Jiles-Atherton model using only symmetrical hysteresis loops - Hahn, Ingo; Lindner, Andreas; et al. (IECON 2013, 2013)
UnivIS-Import:2015-04-16:Pub.2013.tech.IE.LEEAS.asimpl

A Survey on Reliability Assessment of Power Modules - Khoshzaman, Shima; Hahn, Ingo (2018 International Symposium on Power Electronics, Electrical Drives, Automation and Motion (SPEEDAM), 2018)
The continuous increase in the requirements of power modules in industrial applications is the motivation to draw more attention towards reliability and the state-of-health assessment of them. The basics of conventional module packaging technology containing base plate, bond wires and solder layers and its limitations are reviewed in this paper. Typical end-of-life package-related failures are discussed. In addition, accelerated aging tests and common lifetime estimation models are reviewed.<br
Keywords: Power modules; reliability; accelerated aging test; lifetime estimation

Auswertung magnetischer Eigenschaften von Permanentmagneterregten Synchronmaschinen zur geberlosen Regelung, Innovative Klein- und Mikroantriebstechnik - Reill, Josef; Piepenbreier, Bernhard; Hahn, Ingo (ETG/GMM, 2010)
UnivIS-Import:2015-04-16:Pub.2010.tech.IE.LEEAS.auswer

Axially Stacked Multiphase Flux Reversal Machine - Ryu, Jaeho; Hahn, Ingo (45th Annual Conference of the IEEE Industrial Electronics Society (IECON), 2019)
CRIS-Team WoS Importer:2020-05-15

Calculation of Active Material's Torque Contributions for a Flux Switching Machine - Kurtovic, Haris; Hahn, Ingo (IEEE Transactions on Magnetics, 2020)
A new calculation method for the torque contribution of an arbitrary point or element in an electric machine's geometry is developed. The local torque contributions (LTCs) and their visualizations provide insights into the iron utilization and possible machine geometry improvements. The flux tubes created from the magnetic vector potential's equipotential lines are interpreted as a set of local magnetic circuits (LMCs). Each LMC that crosses the air gap contributes to the machine's torque, which is quantifiable by applying the Maxwell stress tensor to the LMC's air-gap intersections. The torque contributions are mapped to all finite elements belonging to each LMC, for each transient calculation's rotor step. Furthermore, the torque contribution data are briefly discussed and a harmonic analysis is performed, focusing on the mean and ripple components of the torque. Finally, a brief example of a topological optimization with the calculated torque contributions as optimization criteria is presented and evaluated.
CRIS-Team Scopus Importer:2020-02-11
Keywords: Electromagnetic torque; flux switching machine (FSM); magnetic circuit; Maxwell stress tensor

Comparative Analysis of Surface Mounted and Flux Focusing Type Axial Flux Permanent Magnet Motor - Syed, Qurban Ali Shah; Hahn, Ingo (PEMD, 2016)
UnivIS-Import:2017-12-18:Pub.2016.tech.IE.LEEAS.compar
Keywords: Axial flux machines; Comparative analysis; Direct drive applications; Flux focusing; High torque density

Comparison of different noise analysis methods for error detection on induction machines - Stiller, Matthias; Wagner, Johannes; Thyroff, Dominik; Hahn, Ingo (2017 IEEE 11th International Symposium on Diagnostics for Electrical Machines, Power Electronics and Drives (SDEMPED), 2017)
Increasing levels of noise and vibration are early indicators for an evoluting error or defect on an electrical machine. There are many different approaches in monitoring the health of an electrical machine, e.g. noise-, vibration- or current-based methods. This paper investigates and compares different methods for noise analysis. Each method provides an own representation of the analysed signal. Therefore, the presented methods are compared regarding their suitability in analysing electrical machines. In the following sections, first the theory behind all methods is presented. Later on, selected error states are re-enacted using an induction machine. Finally, utilizing measured noise and acoustic signals allows assessing the presented methods.
Keywords: error detection; noise analysis; vibration analysis; analysis methods; Fourier transform; cepstrum; Hilbert-Huang-transform; signal-based methods; induction machine

Comparison of Soft Magnetic Composite (SMC) and Electrical Steel - Böhm, Andreas; Hahn, Ingo (Proceedings 2012 2nd International Electric Drives and Production Conference, 2012)
UnivIS-Import:2015-04-16:Pub.2012.tech.IE.LEEAS.compar

Comparison of the Power Factor of SMPM and SM Vernier Outer Runner Machines for Traction Applications - Thyroff, Dominik; Hittinger, Christoph; Hahn, Ingo (2018 IEEE International Magnetics Conference (INTERMAG), 2018)
Low voltage traction applications demand high torques at low speeds and at a small design space. In order to achieve high torque densities, manufacturers often combine high-speed machines with mechanical gearboxes. In the past decade, flux modulation machines came up, offering low speeds and high torque densities by utilizing the magnetic gearing effect. The idea is to remove the mechanical gear and get a compact direct drive solution. Now, the Vernier machines are a subgroup of the flux modulation machines. However, literature reports very poor power factors for Vernier machines in comparison to PM machines as the main drawback. Nevertheless, the presented studies always assume a fixed speed and only one single current operating point. This is correct for fixed speed applications, e.g. pumps and blowers, but it is not correct for traction applications, because the machine cycles dynamically through the torque-speed curve. Therefore, this paper first investigates the machine design requirements considering the machine control strategies and the needs of traction applications. Furthermore, a method to check if the design fulfills the given requirements by calculating only a single operating point is presented. In addition, the emerging differences between Vernier and PM machines are explained using analytic results. Furthermore, the paper presents a power factor comparison of torque optimized Vernier and PM machines while considering iron losses. Thereby, the comparison covers the whole torque-speed range, including the field weakening are
Keywords: finite element analysis; gears; machine control; magnetic flux; permanent magnet machines; power factor; rotors; torque; traction; machine cycles; torque-speed curve; machine design requirements; machine control strategies; single operating point; PM machines; power factor comparison; torque optimized Vernier; torque-speed range; SM Vernier outer runner machines; low voltage traction applications; high torques; low speeds; design space; high torque densities; high-speed machines; mechanical gearboxes; flux modulation machines; magnetic gearing effect; mechanical gear; compact direct drive solution; fixed speed; single current operating point; Torque; Reactive power; Magnetic flux; Gears; Trajectory; Couplings; Modulation; Vernier machine; power factor; control strategy; performance comparison

Comparison of the Resistance- and Inductance-Based Saliency of a PMSM due to a Short-Circuited Rotor Winding - Graus, Johannes; Rambetius, Alexander; Hahn, Ingo (International Power Electronics Conference - ECCE Asia (IPEC 2014), 2014)
Sensorless position estimation based on signal-injection methods always requires a resistance- or inductance-based anisotropy. Therefore, a short-circuited electrical winding can be attached on the rotor. As will be derived in this paper, this method leads to both a resistance- and inductance-based saliency. By an experimental test setup, both saliencies are analyzed and compared towards their accuracy and frequency-dependence. Thereby, for the resistance-based saliency a characteristic behavior is found that can be explained by the interaction between the rotor winding and the eddy current effect. © 2014 IEEE.
UnivIS-Import:2015-04-16:Pub.2014.tech.IE.LEEAS.compar
Keywords: Eddy currents; interior permanent magnet (IPM) motor; ringed pole; sensorless control

Control Algorithms for Matrix Converters With Low Mathematical Complexity - Igney, Jens; Hahn, Ingo (21st International Symposium on Power Electronics (Ee), 2021)
Due to the degrees of freedom inherent in matrix converter modulation, there are a large number of different, seemingly contradictory modulation strategies. This work contributes to a systematization of at least a subset of the strategies. For this purpose, a systematic derivation of direct control algorithms is performed. "Direct" is meant in the sense that the duty cycles are computed using only basic arithmetic. Since such algorithms do not invoke mathematical library functions, they can be easily implemented in embedded processors or programmable logic.Due to their direct computability and systematic derivation from theory, the algorithms can be regarded as archetypes of matrix converter modulation and can be a valuable aid in comparing different control algorithms.
Keywords: Systematics; Program processors; Modulation; Power electronics; Libraries; Complexity theory; Classification algorithms; Matrix converters; Algorithm; Classification

DC-link current and torque ripple optimized self-sensing control of interior permanent-magnet synchronous machines - Chen, Lei; Götting, Gunther; Hahn, Ingo (ICEM, 2016)
To minimize the ripple on the dc-link current and torque due to carrier signal injections, conventional saliency-based self-sensing control schemes using voltage and current carrier signals for interior permanent magnet synchronous machines (IPMSMs) are optimized in this paper. Acoustic noise and efficiency of the self-sensing drive can also be enhanced. Carrier signal oriented coordinates are introduced to model the high frequency behavior of IPMSMs and are used for the analysis and the signal processing of proposed methods. Moreover, stability issues are discussed in this study. Experimental results on a commercial high voltage inverter confirm the applicability of the proposed methods.
UnivIS-Import:2017-03-24:Pub.2016.tech.IE.LEEAS.dclink
Keywords: Carrier Signal Injection; dc-link current ripple; Permanent-Magnet Synchronous Machine; Self-Sensing; torque ripple

Design of a lightweight toroidal FSPM with large air-gap - Lindner, Andreas; Hahn, Ingo (IEEE Workshop on Electrical Machines Design, Control and Diagnosis (WEMDCD 2015), 2015)
UnivIS-Import:2015-10-26:Pub.2015.tech.IE.LEEAS.design

Design of an E-core flux-switching permanent magnet machine with large air-gap - Lindner, Andreas; Hahn, Ingo (IEEE IEMDC 2015, 2015)
UnivIS-Import:2015-10-26:Pub.2015.tech.IE.LEEAS.design_5

Determination of Differential Inductances of Permanent Magnet Synchronous Machines for Sensorless Control - Hahn, Ingo; et al. (International Electric Machines and Drives Conference 2011 (IEMDC 2011), 2011)
This paper presents a novel approach for measuring the differential inductances in a permanent magnet synchronous machine (PMSM). The knowledge of their accurate values is a prerequisite for sensorless vector controlled systems with carrier signal injection. For the measurements a standard industrial power converter is used. Besides the determination of self-inductances in the rotor-fixed reference frame, the measurement of the cross-coupling differential inductances namely the cross saturation is a main part. A high frequency sine signal injection method is used for this purpose. The measurement is compared with the result of FEM calculations. In the second part the influence of the rotor position and the machine load in steady state on the high frequency current amplitude in the quadrature axis is analysed, while the signal is only injected in the direct axis. The results of these measurements are compared with saturation effects in the machine. © 2011 IEEE.
UnivIS-Import:2015-04-16:Pub.2011.tech.IE.LEEAS.determ
Keywords: differential cross-saturation inductances; high frequency injection method; Permanent magnet synchronous machine; rotor position dependency; sensorless control

Deterministic winding function model for slotted induction machines validated by air gap magnetic field measurements - Stiller, Matthias; Hahn, Ingo (IECON 2021 – 47th Annual Conference of the IEEE Industrial Electronics Society, 2021)
This paper deals with a deterministic and analytic winding function model for the calculation of the magnetic field inside the air gap of a squirrel cage induction machine (SCIM). Therefore, a voltage equation system is built up, containing fundamental and harmonic voltage and current waves. After solving the system for the current values with a given voltage excitation, a conclusion on the magnetic field is possible. Furthermore, an approach to consider slotting is used. As validation, measurements are taken within the machine air gap, using a flexible printed circuit containing search coils.

Differential magnetic anisotropy - prerequisite for rotor position detection of PM-synchronous machines with signal injection. - Hahn, Ingo (Proceedings 2010 First Symposium on Sensorless Control for Electrical Drives (SLED), 09./10., 2010)
It is well known that rotor position detection at very low speed and at standstill is only possible with signal injection methods, because at vanishing speed the different methods using the induced voltage (back EMF methods) are not suitable. All signal injection methods need as a prerequisite the existence of a magnetic anisotropy of the machine over a wide range of operating conditions. This document presents first the basic theory of electrical machines to derive the needed machine properties which are the prerequisite for rotor position detection at standstill with signal injection methods. Different machine designs with concentrated windings will be analyzed in view of the differential magnetic anisotropy by means of finite element field calculations. Results from prototype measurements will also be presented and compared with the theoretical findings. © 2010 IEEE.
UnivIS-Import:2015-04-16:Pub.2010.tech.IE.LEEAS.differ
Keywords: Concentrated winding; Cross saturation; Differential magnetic anisotropy; Distributed winding; Field oriented control; Permanent magnet synchronous machine; Sensorless position detection; Signal injection method

Different Iron Loss Models for Electrical Steel Sheets considering Harmonic Flux Signals - Stiller, Matthias; Hahn, Ingo (IEEE International Symposium on Industrial Electronics, 2019)
The type and quality of electrical steel sheets plays an important role for the operating behavior of an electrical machine. Already during the design process of an electrical machine, the electromagnetical properties of the steel sheets and, thus, their contributions to the overall losses must be considered. Therefore, it is necessary to have a simple but also accurate method for approximating the iron losses. However, the flux density in the iron parts of an electrical machine is assumed not to be sinusoidal, whereas classical iron loss models only take sinusoidal waveforms into account. Though, several approaches try to consider also the effects of higher harmonics. This paper compares different well-known loss models for the use with arbitrary flux density waveforms.
CRIS-Team Scopus Importer:2019-08-23
Keywords: arbitrary signals; Bertotti; GSE; hysteresis losses; IEM; iGSE; iron loss models; Jordan; MSE; NSE; Steinmetz

Double stator and single rotor type single-phase flux switching axial flux permanent magnet motor - Syed, Qurban Ali Shah; Kurtovic, Haris; Hahn, Ingo (20th International Conference on Electrical Machines and Systems, ICEMS 2017, 2017)
Keywords: Axial flux permanent magnet motor (AFPM); Flux switching; Self-starting torque; Single-phase

Dynamic On-State Resistance Characterization of GaN FET under Hard-Switching Conditions - Khoshzaman, Shima; Tang, Yikai; Hahn, Ingo (IECON 2021 – 47th Annual Conference of the IEEE Industrial Electronics Society, 2021)
Replacing the conventional silicon-based transistors with the Gallium Nitride High Electron Mobility Transistors (GaN HEMTs) promises higher power densities, switching frequencies and system-level efficiencies due to their significantly superior material properties. Despite the very low static on-state resistance due to the high-density two-Dimensional Electron Gas (2DEG) with high electron mobility, GaN HEMTs suffer from the increased on-state resistance right after switching from the off-state high-voltage to the low on-state voltage, due to charge trapping effects. This phenomenon, also known as current collapse, causes increased power losses in the GaN FET and may lead to reliability issues. In this paper, the dynamic on-state resistance characterization of a 100 V commercially available enhancement mode GaN FET is investigated experimentally for various operating points. The results are compared to those of a Si-based MOSFE
Keywords: gallium nitride (GaN); wide bandgap devices; dynamic on-state resistance; clamping circuit

Effect of particle size and size distribution on the permeability of soft magnetic liquid silicone rubber composites - Schubert, Dirk W.; Werner, Siegfried; Hahn, Ingo; Solovieva, Veronika (Composites Science and Technology, 2019)
Magnetic composites made of LSR (Liquid Silicone Rubber) and a magnetic filler have been investigated with respect to magnetic field guidance for transcutaneous energy transport. Effects of particle size and size distribution on the effective initial magnetic permeability are analyzed. A simple model is presented to describe the permeability as a function of the degree of filling, particle size and size distribution. From this, a calculus for the relevant size average of the filler was developed at 20 vol% of magnetic filler. The calculus showed self-consistency and can be used to tailor optimized powders for better field guidance.
Keywords: polymer matrix composite; magnetic properties; modelling; powder processing

Energy-Efficient Motion Planning for Electrical Drives - Hosseini, Sara; Hahn, Ingo (2018 IEEE Electrical Power and Energy Conference (EPEC), 2018)
The energy consumed over a limited operation time of an electrical drive has a huge impact on the energy consumption in a production line, and therefore, affects directly the economics of a factory or company. Although polynomial interpolation with cubic, quartic or quintic polynomials has been widely used in the literature for motion planning purposes, these polynomials have also some major drawbacks. One of these drawbacks is an insufficient smooth trajectory profile. The other problem is not having adequate equations to solve the problem of using seventh-order polynomials for pre-specified positions, velocities, accelerations and jerks in every specified control points or time intervals during the desired path. Instead, seventh-order or higher-order-polynomials are used to satisfy more boundary conditions to overcome the problem of specifying desired position, velocity, acceleration and jerk at the specified control points. Another method that is used for the trajectory planning, is to use spline interpolation polynomials. A comparison between different methods will be done, and their impact on the overall energy consumption of the system will be discussed.<br
Keywords: Trajectory; Acceleration; Boundary conditions; Planning; Energy consumption; Cost function; Hysteresis motors; Energy efficiency; control points; motion planning; spline interpolation

Entkopplung von Stellsignalen in kontinuierlichen Fertigungsanlagen durch Vorsteuerung - Göb, Mario; Hahn, Ingo (Bahnlaufseminar 10, 2009)
UnivIS-Import:2015-04-16:Pub.2009.tech.IE.LEEAS.entkop

Examining the unstable behaviour of a phenomenological three dimensional, dipole-based hysteresis model - Wagner, Johannes; Hittinger, Christoph; Hahn, Ingo (20th International Conference on Electrical Machines and Systems, ICEMS 2017, 2017)
Keywords: Dipole-Collective; Hysteresis Modell; Field Computation; Magnetic Materials

Finite-Difference-Time-Domain (FDTD) Algorithm for Multiblock Grids - Hahn, Ingo; Kräck, Veronika (ICEM 2014, 2014)
In this paper, a finite-difference time-domain (FDTD) algorithm for multiblock grids is presented to solve electromagnetic field problems. In order to compute the magnetic field distribution in the presence of complex geometries, multiblock grids are used instead of conventional cartesian single-block grids for discretization. Those multiblock grids are globally unstructured, but locally structured. For the implementation of such grids the exchange of information across block interfaces is essential. Simulations of electromagnetic field problems using the multiblock FDTD formulation demonstrate the validity of the method.
UnivIS-Import:2015-04-16:Pub.2014.tech.IE.LEEAS.finite
Keywords: block communication; finite-difference time-domain (FDTD) method; multiblock grid; multiblock solver

Geberfehlerüberwachung mit Hilfe signalinjizierender Verfahren im Stillstandsfall - Hahn, Ingo; et al. (SPS/IPC/DRIVES, 2011)
UnivIS-Import:2015-04-16:Pub.2011.tech.IE.LEEAS.geberf

Heuristic structural optimization of the permanent magnets used in a surface mounted permanent magnet synchronous machine - Hahn, Ingo (IEEE Transactions on Magnetics, 2012)
Structural optimization, as the process of finding an optimal material distribution of a machine part, is known from the mechanical engineering, but in the field of the design of electrical machines only few dedicated applications of that method have been reported yet. Most described applications are electromagnetic actuators. This report deals with the problem of finding an optimal structure of the permanent magnets used within a surface mounted permanent-magnet synchronous machine. In contrast to other reported methods, which use continuous models to describe the material properties with a postponed homogenization process, this paper will present a possible solution to the structural optimization problem by a simple heuristic search algorithm. For that purpose, the preselected design area is discretized with suitable quadrilateral cells. The material properties of each cell are set by a simple heuristic search algorithm, while the material properties are chosen from a discrete set of material properties. Therefore, the resulting problem is a discrete optimization problem. The finite-element method is used to solve the magnetic field equations and to gain information about the optimization performance index for each material distribution variant occurring during the optimization process. © 2006 IEEE.
UnivIS-Import:2015-03-09:Pub.2012.tech.IE.LEEAS.heuris
Keywords: Composite materials; heuristic search algorithm; machine design; optimal material distribution; permanent-magnet synchronous machine; structural optimization; topology optimization

Hybrid Method for Topology Optimization Based on a Meta-Heuristic Method and Pixel Connectivity - Ruzbehi, Shabnam; Hahn, Ingo (IET-PEMD, 2020)
One of the recent developments in engineering optimization is the topology optimization. This method is common in mechanical engineering and optimization of mechanical structures, but it can be used to design novel structures of the electromagnetic devices and electrical machines. In general, topology optimization results need a further development or post-processing to gain a device, which is more adapted to the manufacturing process. Therefore, a hybrid optimization method is offered, which is based on a meta-heuristic method like the Genetic Algorithm (GA). Because of irregular shapes of the optimized topologies, a local method, called pixel connectivity technique, is presented to regularize the structure in a two-level optimization with a focus on the improvement of the meta-heuristic method via GA and post-processing inspired by an image processing method. The Finite Element Method is used to analyse a well-known E-core actuator developed by applying the proposed topology optimization method as a case study. The optimization goal is to achieve the greatest savings of material and gain a lighter weight of the device, while preserving the electromagnetic force at an appropriate level. It is possible to extend and apply this proposed method to different active components of electrical machines in combination with other goals.<br
Keywords: TOPOLGY OPTIMIZATION; PIXEL CONNECTIVITY; REGULARIZATION METHOD; BINARY METHOD; HYBRID METHOD.

Hybrid Structure Optimization of a PMSM Using Global and Local Methods for Higher Torque and Lower Volume - Ruzbehi, Shabnam; Hahn, Ingo (11th IEEE International Conference on Renewable Energy Research and Applications, ICRERA 2022, 2022)
In this work, a Structure Optimization procedure of a permanent magnet synchronous motor is shown, based on a hybrid method to gain a lower weight structure, lower torque ripple and cogging torque, and to preserve the torque as high as possible. As structure optimization is faced with a highly complex structure, to overcome this drawback a hybrid optimization method using a global and a local method is suggested. This hybrid method not only gains a smoother structure but also gains better technical results with considerable reduction of calculation time compared to non-hybrid simple optimization. The proposed hybrid method validity is approved on the rotor and permanent magnet (PM) part of a permanent magnet synchronous motor. The results lead to material and cost reduction, from another side to an improvement of the flux linkages and back-EMF waveforms. Also, torque ripple and cogging torque reduction lead to lower vibration and acoustic noise.
CRIS-Team Scopus Importer:2022-12-02
Keywords: Genetic algorithms; PMSM; Sensitivity method; Topology optimization; Torque; Torque ripple

Identification of time-variant high frequency parameters for sensorless control of PMSM using an internal model principle based high frequency current control - Seilmeier, Markus; Böhm, Andreas; Hahn, Ingo; Piepenbreier, Bernhard (2012)
Standstill and low speed self-sensing based field oriented control of PMSM using the high frequency signal injection method requires a sufficient saliency ratio of the high frequency differential inductances of the machine. Therefore these inductances need to be known precisely to be able to guarantee stability of the sensorless control. In order to perform the identification, the conventional field oriented control scheme is extended by additional PI-type controllers in a positive and negative sequence high frequency coordinate system, thus resulting in zero steady state control error in case of superimposed sinusoidal high frequency test current reference values. Moreover the extended control scheme provides a direct demodulation of sine and cosine parts of the high frequency control signals and therefore enables a direct identification of all model parameters relevant for HF injection based sensorless control (differential self-and mutual inductances and high frequency resistances). In contrast to conventional methods, no prerequisites for the parameters or its' dependencies have to be fulfilled.
Keywords: nonlinear coordinate transformation; differential inductances; field-oriented control; internal model principle; parameter identification; PMSM; sensorless control; test current control

Identification of time-variant high frequency parameters for sensorless control of PMSM using an internal model principle based high frequency currrent control - Böhm, Andreas; Seilmeier, Markus; Hahn, Ingo; Piepenbreier, Bernhard (20th International Conference on Electrical Machines, 2012)
UnivIS-Import:2015-04-16:Pub.2012.tech.IE.LEEAS.identi

Identifikation des Materialbahnverhaltens in kontinuierlichen Fertigungsanlagen - Göb, Mario; Hahn, Ingo (SPS/IPC/DRIVES, 2010)
UnivIS-Import:2015-04-16:Pub.2010.tech.IE.LEEAS.identi_9

Impact of Bridge-Saturation on Anisotropy-Based Initial Rotor Polarity Detection of Interior Permanent-Magnet Synchronous Machines - Hahn, Ingo; Götting, Gunther; Chen, Lei; Rötzer, Marco (ICEMS, 2016)
Anisotropy-based initial rotor polarity detection of interior permanent-magnet synchronous machines (IPMSM) relies typically on the saturation in the stator iron. The current response to a voltage pulse into the north pole (d+) direction of the magnet should be higher in magnitude than into the opposite direction because of increased stator saturation. However, experiments show sometimes an opposite result. The present paper considers the bridge-saturation in the rotor to explain this phenomenon. Finite element (FE) analyses of six modified PMSM models demonstrate that the bridge-saturation decreases, as the flux linkage begins to increase. That leads to an increase of the differential inductance if the stator iron is not strongly saturated. The impact of the machine geometry parameters on the differential inductance is also studied in this paper by means of a sensitivity analysi
UnivIS-Import:2017-03-24:Pub.2016.tech.IE.LEEAS.impact

Improved Accuracy of Sensorless Position Estimation by Combining Resistance- and Inductance-Based Saliency Tracking - Graus, Johannes; Hahn, Ingo (IECON 2015, 2015)
UnivIS-Import:2016-06-01:Pub.2015.tech.IE.LEEAS.improv

Improved Sensorless Position Estimation of an IPMSM by Weighted Combination of Resistance-and Inductance-Based Saliency Tracking - Hittinger, Christoph; Hahn, Ingo (2018 21st International Conference on Electrical Machines and Systems (ICEMS), 2018)
Keywords: Rotors; Inductance; Resistance; Estimation error; Windings; Saturation magnetization; sensorless control; single-tooth winding; short-circuited rotor winding

Influence of Elementary Model Parameter Variations on Simulated Ferromagnetic Hysteresis Using a Ring-Shaped 3D Dipole Collective - Hittinger, Christoph; Wagner, Johannes; Hahn, Ingo (Electrical Machines and Systems (ICEMS), 2017 20th International Conference on, 2017)

Influence of geometric parameters and cutting edge deterioration on the differential inductances. - Hahn, Ingo; Böhm, Andreas (IEEE International Symposium on Sensorless Control for Electrical Drives (SLED 2014), 2014)
A prerequisite for self-sensing field oriented control of PMSM for standstill operation is a sufficient saliency ratio (magnetic anisotropy) of the differential inductances over the desired operating area. High frequency injection methods are very common in order to perform saliency tracking based self-sensing operation. Vanishing saliency for certain operating points or a change of the sign of the inductance difference, which needs to be known for the self-sensing algorithm, causes loss of stability of the self-sensing control method. This paper uses a simple, parameterized Finite-Element model in order to simulate the influence of geometric parameters and cutting edge deterioration. The simulations have shown that the cutting edge deterioration has only a slight influence on the saliency ratio of the differential inductances, although worst case conditions are assumed for the deterioration. This result is verified on a FE-model of a real PMSM. The most significant influence on the saliency ratio derives from the size of the tooth tip. For low ratios between stator yoke height and tooth width the area with vanishing magnetic anisotropy is increased. The area of magnetic anisotropy is increased with the width of the magnets, however the value of the anisotropy is decreased for large magnet widths. © 2014 IEEE.
UnivIS-Import:2015-04-16:Pub.2014.tech.IE.LEEAS.influe
Keywords: cutting edge deterioration; differential inductances; geometric parameters; magnetic anisotropy

Influence of Partly Closed Slots on the Differential Inductances - Graus, Johannes; Seilmeier, Markus; Hahn, Ingo; et al. (SLED, 2012)
A prerequisite for sensorless field oriented control of permanent magnet synchronous machines (PMSMs) at very low speed and standstill operation using signal injection methods is a sufficient saliency ratio of the differential inductances throughout the desired operating area. High frequency signal injection methods are very common in order to perform saliency tracking based sensorless operation. Vanishing saliency for certain operating points or a change of the sign of the difference of the differential inductances, which needs to be known for the sensorless algorithm, causes the loss of stability of the sensorless control method. A closed or partly closed stator slot geometry tends to show a local current dependent loss of the saliency even for low currents. This phenomenon typically shows up as a star-shaped pattern of the inductance surface as discussed further within this paper. © 2012 IEEE.
UnivIS-Import:2015-04-16:Pub.2012.tech.IE.LEEAS.influe_7
Keywords: Closed slots; differential inductances; permanent synchronous machine; sensorless position detection; standstill operation

Influence of Stator Saturation on the Differential Inductances of PM-Synchronous Machines with Concentrated Winding - Graus, Johannes; Hahn, Ingo; et al. (SLED 2012, 2012)
For sensorless position detection of permanent magnet synchronous machines at very low speed and standstill, signal injection methods are commonly used. As a prerequisite these so called saliency-tracking methods require a differential magnetic anisotropy of the machine, which is both position and load dependent and thus varying during operation. So the performance of sensorless operation strongly depends on the machine design. To investigate the influence of the stator saturation a machine model based on a magnetic equivalent circuit is presented in this document. This model is then used to analyze the differential inductances of a machine with concentrated windings. The results show that for some angles of the current vector the inductances do not vanish even for high currents. This phenomenon is explained by analyzing the flux paths. © 2012 IEEE.
UnivIS-Import:2015-04-16:Pub.2012.tech.IE.LEEAS.influe
Keywords: concentrated winding; cross saturation; differential magnetic anisotropy; magnetic equivalent circuit; permanent magnet synchronous machine; sensorless position detection

Influence of the Magnetic Bridges on the Flux Focusing Type Axial Flux Permanent Magnet Motor - Syed, Qurban Ali Shah; Hahn, Ingo (2018 IEEE Electrical Power and Energy Conference (EPEC), 2018)

Influence of Turning on the Magnetic Properties of Electrical Steel in the Production of Electrical Machines - Böhm, Andreas; Hahn, Ingo (International Electric Machines and Drives Conference 2011 (IEMDC 2011), 2011)
This paper presents a method to determine the influence of a turning process on the magnetic properties of non-orientated electrical steel sheets. This is done by measuring the magnetization curve of ring specimens by using them as a kind of transformer core. The magnetization curve can be calculated by measuring the current on the primary side and the voltage on the secondary side which has opened clamps. To determine the influence of the turning process two approaches are considered. The first one compares two turned ring specimens of which one consists of two concentric rings so that the cutting length is doubled. The second approach compares a turned ring specimen with a laser and a water jet cut specimen. The measurements have shown that turning has only a slight influence on the magnetic properties. It is about the same as water jet cutting and less than laser cutting for low field strengths. © 2011 IEEE.
UnivIS-Import:2015-04-16:Pub.2011.tech.IE.LEEAS.influe
Keywords: Electrical steel; laser cutting; magnetic properties; turning; waterjet cutting

Investigation of a large air-gap E-core flux switching machine with arbitrary magnet shape and grain-oriented material - Lindner, Andreas; Hahn, Ingo (ICEM`2016, 2016)
UnivIS-Import:2017-01-09:Pub.2016.tech.IE.LEEAS.invest

Investigation of an Electrically Excited Vernier Machine with a Concentrated Winding intended for Traction Applications - Thyroff, Dominik; Hahn, Ingo (2019 26TH INTERNATIONAL WORKSHOP ON ELECTRIC DRIVES: IMPROVEMENT IN EFFICIENCY OF ELECTRIC DRIVES (IWED) PROCEEDINGS, 2019)
CRIS-Team WoS Importer:2019-06-18

Investigation of parametrized curves for the pole shaping in an E-core Flux-Switching Machine with large air-gap - Kurtovic, Haris; Hahn, Ingo; Lindner, Andreas (PEMD, 2016)
UnivIS-Import:2017-12-18:Pub.2016.tech.IE.LEEAS.invest_6
Keywords: Electromagnetic performance; Flux-switching permanent magnet machine; Large air-gap; Spline shaped magnetic core; Switched flux machine

Investigation of the Influences of the bandwidths in Hysteresis current controller on single phase inverters - Hazrati, Tina; Hahn, Ingo (2024 International Symposium on Power Electronics, Electrical Drives, Automation and Motion, SPEEDAM 2024, 2024)
At the present time, due to climate change and global warming, reducing the energy consumption of electrical drives is a necessity. According to the advanced technological improvement of power electronics devices, the hysteresis current control techniques (HCC) has been widely used for small systems because of their simple implementation and excellent dynamic performance. Moreover, owing to their simplicity, insensitivity to load parameters' variations, fast dynamic response and inherent maximum current limiting characteristics, hysteresis current control is a rather popular one among different current control techniques. This paper investigates the influence of the hysteresis bandwidth of a two-level single-band controller with predefined target current amplitude and DC-voltage on the total dissipated energy and the current's THD of a single-phase system. The simulation model of the simple passive inductive-resistive network and the power inverter with the idealized switches (here: SiC MOSFETs) have been implemented in Scilab 6.0.2 simulation environment. The obtained results suggest not to use only a narrow hysteresis bandwidth but also lower current amplitudes and lower DC voltages depending on the application.
CRIS-Team Scopus Importer:2024-08-30
Keywords: DC-voltage; hysteresis bandwidth; hysteresis current controller (HCC); total harmonic distortion (THD)

Investigation on different pole configurations of an outer rotor integrated magnetic gear - Thyroff, Dominik; Hahn, Ingo (IECON 2017 - 43rd Annual Conference of the IEEE Industrial Electronics Society, 2017)
In contrast to conventional permanent magnet machines, integrated magnetic gears exhibit different pole pairs in the stator and the rotor. Consequently, a flux modulation of the air gap magnetic field is necessary for torque transmission, wherefore additional flux modulation poles (FMPs) are used. As the number of FMPs adopts to the pole configuration of the stator and the rotor, arbitrary combinations of both are possible. This results in new degrees of freedom in the machine design process, wherefore this paper studies the advantages and disadvantages of a wide range of different stator and rotor pole configurations.
Keywords: air gaps; magnetic fields; magnetic gears; permanent magnet machines; rotors; stators; torque; air gap magnetic field; different stator; machine design; magnetic gear; outer rotor; permanent magnet machines; rotor pole; torque; Iron; Magnetic flux; Rotors; Stator windings; Torque; Integrated magnetic gear; Vernier machine; iron loss; machine design; pole configuration

Investigations on the Concept of Short-Circuited Rotor Windings for the Improvement of the Self-Sensing Capability of Electrical Machines - Hittinger, Christoph; Hahn, Ingo (2019 26TH INTERNATIONAL WORKSHOP ON ELECTRIC DRIVES: IMPROVEMENT IN EFFICIENCY OF ELECTRIC DRIVES (IWED) PROCEEDINGS, 2019)
CRIS-Team WoS Importer:2019-06-18

Kinodynamic Motion Planning and Energy Loss Cost Function Modelling for a 2- DOF Robot Arm Manipulator - Hosseini, Sara; Hahn, Ingo (Proceedings of the IEEE International Conference on Industrial Technology, 2020)
This paper proposes an energy efficient motion planning for industrial robots with a novel cost function formulation. The dynamics of the 2-DOF (degree of freedom) robot arm manipulator, models the inertia and mass related losses, Coriolis and centrifugal losses of each link, friction losses and losses related to the gravity. A DC motor is used in each joint to drive the manipulator. For the point-to-point (PTP) trajectories, a fifth order polynomial is considered. Furthermore, the torque analysis with respect to the already mentioned loss terms is done and its effect on the overall electrical and mechanical losses is discussed. These torques and losses analyses are gained by the forward dynamics and inverse kinematics of the 2-DOF manipulator. In the last part, the simulation results of the power losses cost function (PLCF) with respect to the terms associated to velocity and acceleration of each link in every single time instant of the motion is modelled.
CRIS-Team Scopus Importer:2020-05-12
Keywords: Energy losses; Forward dynamics; Inverse kinematics; Polynomial; Power losses cost function; Robots

Kriging-Assisted Multi-Objective Particle Swarm Optimization of Permanent Magnet Synchronous Machine for Hybrid an Electric Cars - Bittner, Florian; Hahn, Ingo (IEMDC 2013, 2013)
In this paper a novel combination of a multi-objective particle swarm optimization algorithm and a Kriging metamodel is presented, which is used for the design optimization of a permanent magnet synchronous machine (PMSM) for electric and hybrid cars. As the evaluation of mostly conflicting objective functions requires computational expensive numerical field simulations, a fast converging optimization algorithm which depends on only a few exact evaluations is needed. Instead of running exact calculations on every design the objective values are estimated by means of a Kriging model in advance and only the most promising design candidates are being computed in a more accurate way. Furthermore, good solutions are searched for directly on the metamodel and particles are spawned at the corresponding positions in the parameter space. The performance of the proposed algorithm is investigated with the help of an analytical test case and used for design optimization of a 10 poles PMSM with 11 parameters and 3 objectives. © 2013 IEEE.
UnivIS-Import:2015-04-16:Pub.2013.tech.IE.LEEAS.krigin
Keywords: Electric Car; FEM; Hybrid Car; IPM; Kriging; metamodel; Multi-Objective Optimization; Particle Swarm Optimization; Permanent Magnet Synchronous Machine; PMSM; Pre-evaluation; PSO; Spawning; Surrogate

Magnetic Direction Analysis of Permanent Magnet in a Permanent Magnet Synchronous Machine - Zollet, Bastian; Ruzbehi, Shabnam; Hahn, Ingo (2022 International Symposium on Power Electronics, Electrical Drives, Automation and Motion, SPEEDAM 2022, 2022)
In the optimization of permanent magnet synchronous machines (PMSM), the properties of the magnets play a significant role. The magnetization direction of the permanent magnets is determined during their manufacturing process. By varying the magnetization direction, it is possible to influence the torque and cogging torque delivered by the machine. In the present work, different magnetization patterns are analyzed regarding their effects on these characteristics. The magnetization directions considered are parallel, radial, and parabolic magnetization as well as two different versions of Halbach magnetization. Applying these magnetization directions, torque, torque ripple and cogging torque are determined using simulation in FEMM 4.2 based on the finite element method. During the production of the machines, tolerances inevitably occur that additionally influence these parameters. Selected tolerances are also investigated using the finite element method.
CRIS-Team Scopus Importer:2022-09-02
Keywords: cogging torque; finite element method; magnetization direction; manufacturing tolerances; PMSM; ripple; torque

Magnetization characteristics and loss measurements of the axial flux permanent magnet motor's stator - Syed, Qurban Ali Shah; Solovieva, Veronika; Hahn, Ingo (2019 IEEE International Electric Machines and Drives Conference, IEMDC 2019, 2019)
In this paper, the magnetization characteristics of the stator of the flux focusing type double stator and single rotor (DSSR) axial flux permanent magnet motor (AFPM) are measured and analyzed, using the toroid test setup. The toroid test setup is validated and comparative analysis of the magnetization characteristics of the stacked and tape-wound lamination is carried out. The air-gap flux flows in the axial direction, therefore, the stator of the AFPM should be manufactured by using either the soft magnetic composite (SMC), or the tape-wound electrical steel. The milling technique is adopted to make the slots in the ring, and the iron losses are measured in the slotted and non-slotted structures of the SMC and tape-wound electrical steel. The influence of the physical dimensions, heat-treatment, and gluing of the tape-wound lamination is investigated.
CRIS-Team Scopus Importer:2019-08-30
Keywords: Axial flux motor; Core loss; Heat-treatment; Magnetization characteristics; SMC; Tape-wound lamination

Measurement of Magnetic Properties of Steel at High Temperatures - Böhm, Andreas; Hahn, Ingo (IECON 2014, 2014)
UnivIS-Import:2015-04-16:Pub.2014.tech.IE.LEEAS.measur

Measurement of rare earth magnets at high temperatures - Lindner, Andreas; Hahn, Ingo (SPEEDAM, 2016)
UnivIS-Import:2017-01-09:Pub.2016.tech.IE.LEEAS.measur
Keywords: Magnetic measurement; Permanent Magnet Drives; Rare earth magnets; Temperature behavior

Model Based Closed Loop Control Scheme for Compensation of Harmonic Currents in PM-Synchronous Machines - Seilmeier, Markus; Arenz, Stefan; Piepenbreier, Bernhard; Hahn, Ingo (SPEEDAM 2010, 2010)
With increasing use of concentrated windings in permanent magnet synchronous machines harmonic effects have to be considered more and more for current control design. A structural expansion of the control scheme is needed to handle these higher harmonics. In this paper an effective method is proposed to carry out an expansion of the control scheme. Firstly the nonlinear disturbances are transformed into new fictitious rotating coordinate systems to get an easier description of the disturbances. The compensation of the harmonics is achieved in the new coordinates by applying closed loop controllers with suitable disturbance models. Therefore the control scheme is robust concerning parameter variations. In order to decouple reference and disturbance response a nonlinear model based dynamic feed forward control is used. The proposed control scheme is proven by test bench measurements. © 2010 IEEE.
UnivIS-Import:2015-04-16:Pub.2010.tech.IE.LEEAS.modelb
Keywords: Compensation of harmonics; Current oscillations; Permanent magnet synchronous machines; Two-degrees of freedom control scheme

Model Based Rotor Angle Fault Detection in PM Synchronous Machines - Hahn, Ingo; et al. (21st International Symposium on Power Electronics, Electrical Drives, Automation and Motion, 2012)
In safety-critical drive applications the knowledge of the rotor position of an electrical machine is essential to prevent damage of men and machines. This paper analyses several model-based rotor angle fault detection methods for permanent magnet synchronous machines (PMSM). Starting with a conventional fundamental wave machine model a method based on Analytical Redundancy Relations (ARR), a Parity Space approach, an observer structure and two simple back emf models are compared for fault detection. The ARR method is established with a graphical structural analysis and the Parity Space method is based on a Groebner basis approach. The observer method and the back emf models utilise conventional techniques. In an additional, part the machine model is extended with the differential mutual inductances to improve the dynamic fault detection characteristics. One back emf method is used to present the advantages of the extended machine model in contrast to the conventional one. © 2012 IEEE.
UnivIS-Import:2015-04-16:Pub.2012.tech.IE.LEEAS.modelb
Keywords: analytical redundancy relations; fault detection; parity space approach; permanent magnet synchronous machine

Modeling and Optimization of a Short-Circuited Rotor Winding of a PMSM for Saliency Tracking - Hahn, Ingo; Graus, Johannes (IEEE International Symposium on Sensorless Control for Electrical Drives (SLED 2014), 2014)
Sensorless position estimation based on signal-injection methods always requires a resistance- or inductance-based anisotropy. Therefore, a short-circuited electrical winding can be attached on the rotor. This paper proposes a simplified machine model by which the influence of one or more short-circuited rotor windings can be calculated and optimized with little effort. Simulations for the optimized rotor winding configurations are presented and compared to measurement results from an experimental machine. © 2014 IEEE.
UnivIS-Import:2015-04-16:Pub.2014.tech.IE.LEEAS.modell
Keywords: permanent magnet motors; ringed-pole; sensorless control; sensorless drives

Modeling integrated magnetic gears using a magnetic equivalent circuit - Thyroff, Dominik; Meier, Stefan; Hahn, Ingo (Industrial Electronics Society, IECON 2015 - 41st Annual Conference of the IEEE, 2015)
This paper introduces an integrated magnetic gear intended as direct-drive. Next, a magnetic equivalent circuit for the presented gear topology is proposed. This approach uses the principle of virtual work for torque calculation and takes magnetic leakage and saturation into account. Thereby, the approach focuses on a reduction of the computation time compared to finite element simulation. Finally, the suggested approach is verified by the results of a finite element simulation.
Keywords: integrated magnetic gear; magnetic equivalent circuit; machine design; magnetic leakage; magnetic saturation; direct-drive; integration

Modeling of an IPMSM with Short-Circuited Rotor Winding for Sensorless Position Estimation by FEA Using the Frozen Permeability Method - Hittinger, Christoph; Hahn, Ingo (Industrial Electronics Society , IECON 2017 - 43rd Annual Conference of the IEEE, 2017)

Modeling Single and Double Stator Axial Eddy Current Brakes Considering Current Displacement, Magnetic Leakage, Fringing and Saturation Using Coupled Electric and Magnetic Equivalent Circuits - Meier, Stefan; Hahn, Ingo (IECON 2014, 2014)
UnivIS-Import:2015-04-16:Pub.2014.tech.IE.LEEAS.modeli_0

Modelling and Examination of the Influence of a Short-Circuited Rotor Winding for Saliency Tracking of a Machine with a Three-Phase Single-Tooth Winding - Hittinger, Christoph; Thyroff, Dominik; Hahn, Ingo (Electric Machines and Drives Conference (IEMDC), 2017 IEEE International, 2017)

Modelling the Influence of the Mechanical Forces on the Commutation Process of a DC Motor - Wagner, Johannes; Hahn, Ingo (IECON 2021 – 47th Annual Conference of the IEEE Industrial Electronics Society, 2021)
The sum of forces acting on the contact layer between a graphite brush and a copper bar has a major influence on its conductivity. Therefore, the current ripple gives a hint to what happens to the commutator during one rotation. In this paper, a conductivity model and a mechanical model are proposed to simulate and evaluate the influence of various forces on the commutation process.
Keywords: Industrial electronics; Brushes; Shape; Commutation; Current measurement; Rotors; Graphite; Contact resistance; DC motors

Modulation Strategy and Control Range Function for Matrix Converters Without Trigonometric Functions - Igney, Jens; Hahn, Ingo (2022 International Symposium on Power Electronics, Electrical Drives, Automation and Motion, SPEEDAM 2022, 2022)
The theory presented in this paper preserves the inherent symmetry of the matrix converter. In this way, analytically simple and computationally inexpensive formulas are derived to describe the control range and modulation of the classic 3×3 matrix converter. No trigonometric formulas need to be evaluated to verify the control range and to calculate the modulation. This is beneficial for the realization of efficient real-time program code.
CRIS-Team Scopus Importer:2022-09-02
Keywords: algorithm; control limits; control range; matrix converter; modulation strategy

Neural network meta-modeling and optimization of flux switching machines - Kurtovic, Haris; Hahn, Ingo (2019 IEEE International Electric Machines and Drives Conference, IEMDC 2019, 2019)
This paper presents the application of neural networks (NN)in the design and optimization of the flux switching machine. A finite element (FE)model of the flux switching machine is used to create data for the training of NNs. The trained NN meta-models are used to predict the properties of machine designs. Subsequently, a preselection from these predictions for further FE calculations is employed. Based on this approach, a generational NN based optimization is implemented. Furthermore, during the optimization many NN topologies and output variable combinations are investigated. The NN predictions and their quality are evaluated according to output variables, generations, and NN layouts. In addition, the improvements in the machine's capabilities are presented using a Pareto-domination based approach.
CRIS-Team Scopus Importer:2019-08-30
Keywords: Flux switching machine; Meta-modeling; Neural networks; Optimization

New single phase flux switching axial flux permanent magnet motor - Syed, Qurban Ali Shah; Kurtovic, Haris; Hahn, Ingo (2017 IEEE International Magnetics Conference, INTERMAG 2017, 2017)

New Single-Phase Flux Switching Axial Flux Permanent Magnet Motor - Syed, Qurban Ali Shah; Kurtovic, Haris; Hahn, Ingo (IEEE Transactions on Magnetics, 2017)
Keywords: Axial flux permanent magnet motor (AFPM); flux switching; single phase; starting torque

Nonlinear Modeling of MGSPMs Based on Hybrid Subdomain and Magnetic Equivalent Circuitry - Dianati, Babak; Hahn, Ingo (IEEE Transactions on Magnetics, 2022)
The need for combining two mechanical powers with electrical power is a vital part of many applications, such as hybrid electric vehicles. The magnetic geared surface permanent magnet (MGSPM) motor is a compact and efficient way of achieving this goal. However, their complex structure demands time-consuming optimizations, which requires a large number of simulations. In this context, a fast and accurate simulation method is required to reduce the design and optimization time. In addition to speed and accuracy in considering the complex structures of the machine, as the saturation effect has a major impact on the accuracy of the simulations in these machines, it must be included in the method. To tackle this problem, in this article, a hybrid subdomain (SD) and magnetic equivalent circuit (MEC) model is proposed, considering the saturation effect of the iron parts using current distributions in the SD model on the surfaces of modulators and rotor core, as well as in the stator slots. These currents are calculated using the MEC model of the respective parts and Ampere's law. Furthermore, an example motor is simulated both using the proposed method and the FE method, and the accuracy of the method both for prediction of magnetic flux density inside iron parts and prediction of flux linkages of the machine for a variety of designs and excitations is verified.
CRIS-Team WoS Importer:2021-12-31

Nonlinear Optimization of Energy Consumption in Trajectory Planning of a Single-axis Electrical Drive - Hosseini, Sara; Hahn, Ingo (IEEE International Symposium on Industrial Electronics, 2019)
The energy conservation for the motion of an electrical drive is an important but yet not well-addressed problem in the field of trajectory planning for motion control in machine tools. The objective of this paper is the formulation of the optimal trajectory planning problem as a nonlinear optimal control problem, and finding a solution by state parameterization for it. This goal is achieved in a direction that the velocity and acceleration profiles taken from the current and frequency of the motor lead to the minimum energy consumption of the electrical drive during specific time duration. An energy model is adopted with respect to the electrical losses in the motor and scheduled the optimal velocity with an optimal control law gained by the calculus of variations method for a constant torque condition in a uniform environment.
CRIS-Team Scopus Importer:2019-08-23
Keywords: calculus of variations; control points; nonlinear energy optimization; Trajectory planning

Numerical modeling for 3D eddy current calculation in magneto-quasistatic approximation - Ryu, Jaeho; Hahn, Ingo (2021 22ND IEEE INTERNATIONAL CONFERENCE ON INDUSTRIAL TECHNOLOGY (ICIT), 2021)
CRIS-Team WoS Importer:2021-09-10

Numerical Modeling for Induced Eddy Current Calculation on a Non-uniform Mesh - Ryu, Jaeho; Hahn, Ingo (TWENTIETH BIENNIAL IEEE CONFERENCE ON ELECTROMAGNETIC FIELD COMPUTATION (IEEE CEFC 2022), 2022)
CRIS-Team WoS Importer:2023-03-24

On Experimental Energy Consumption Estimation of a 6-DoF Industrial UR3e Robot Arm Manipulator in Trajectory Planning - Hosseini, Sara; Hahn, Ingo (IEEE International Workshop on Robot and Human Communication, RO-MAN, 2024)
This paper proposes an energy consumption estimation in the trajectory planning task of an industrial robot (IR) arm manipulator. Human-robot collaborative scheduling has become integral to modern manufacturing. Effective scheduling of human-robot cooperation is crucial for enhancing production efficiency. However, energy-efficient trajectory planning in human-robot interaction remains an unexplored area. To address this, a 6-DoF (Degree of Freedom) robot arm, available in the laboratory, was utilized to assess the energy consumption of this specific robot type. However, his approach can be applied to any robot, whether it's a human-robot collaboration, a mobile robot, or any other articulated robot arm manipulator.For this goal the electrical and mechanical losses of a 6-DoF robot arm manipulator from the company Universal Robots is modeled and its power losses cost function (PLCF) is derived correspondingly to calculate the electromechanical energy losses. The objective of this paper is to estimate the energy losses in a trajectory planning task in cartesian space for a tool center point (TCP) of the robot, starting from an initial point and resting at a final point. This goal is achieved by examining and analyzing the kinematics and dynamics followed by measuring the velocity and acceleration related terms of each motor at each joint of the UR3e robot arm in a laboratory setup. The results estimate the changes of energy losses in the overall trajectory following of the robot manipulator and presents the results of the estimated and measured reduction terms.
CRIS-Team Scopus Importer:2024-11-29
Keywords: electromechanical losses; industrial robot; motion planning; power consumption; six degree of freedom robot

Optimization of the flux modulation poles for Vernier machines with concentrated windings - Thyroff, Dominik; Hahn, Ingo (2017 IEEE Workshop on Electrical Machines Design, Control and Diagnosis (WEMDCD), 2017)
Vernier machines achieve high torque densities and fit the demands of direct drives due to the usage of the magnetic gearing effect. Unfortunately, Vernier machines suffer from a poor power factor. Thereby, in analytic models the power factor depends on the permeance coefficients of the ferromagnetic flux modulation poles (FMPs), thus the FMP shape influences the power factor. Therefore, this paper investigates the optimal FMP shape using a multi-objective genetic algorithm based optimization to gain the Pareto frontier. For that purpose, the algorithm creates the FMP shape autonomously. The results show that an S-shaped sideline of the FMP is beneficial.
Keywords: Pareto optimisation; genetic algorithms; magnetic flux; motor drives; power factor; rotors; FMP shape; Pareto frontier; S-shaped sideline; Vernier machines; concentrated windings; direct drives; ferromagnetic flux modulation poles; flux modulation pole optimization; magnetic gearing effect; multiobjective genetic algorithm based optimization; permeance coefficients; power factor; Magnetic flux; Optimization; Reactive power; Rotors; Shape; Stators; Torque; Vernier machine; genetic algorithm; multi-objective optimization; power factor; tooth shape

Parametric Optimization of Flux Focusing Type Double Stator and Single Rotor Axial Flux Permanent Magnet Motor - Syed, Qurban Ali Shah; Hahn, Ingo (2018 IEEE International Magnetics Conference (INTERMAG), 2018)

Phenomenological Modelling of Ferromagnetic Hysteresis using three Dimensional Dipole Collectives - Wagner, Johannes; Hahn, Ingo; Hittinger, Christoph (ICEM 2016, 2016)
Knowing the magnetic properties of electrical steel is very important to build highly efficient electrical machines. Many approaches, which are either of mathematical, physical or phenomenological kind, were developed in the past in order to predict the phenomenon of hysteresis in case of unmeasured conditions. In this paper, a phenomenological 3D hysteresis model using magnetic dipoles, which are mechanically supported on a 3-dimensional grid, is presented. The different interactions between these dipoles are based on the equations of micromagnetism. Instead of minimizing the free energy in the system by mathematical optimization methods, each elementary dipole is able to rotate into an individual energetically favourable positon due to its mechanical mounting. In the following sections the model, its parameters and the identification process are presented. Afterwards, the results of the parameter identification process for a measured hysteresis are shown. Furthermore the predictive abilities of the model in case of unmeasured conditions are discussed.
Keywords: Dipole-Collective; Micromagnetism; Hysteresis; Hysteresis Modell; Electrical Steel; Ferromagnetism; Field Computation; Magnetic Materials

Post-processing Topology Optimization of an Electromagnetic Actuator Using a Hybrid Method of Genetic Algorithm and Local Importance Measure (LIM) - Ruzbehi, Shabnam; Hahn, Ingo (2019 9th International Conference on Power and Energy Systems, ICPES 2019, 2019)
In the modern design and to improve the operation characteristics of electrical machines and electromagnetic devices an optimal structure of the machine's active and flux guiding parts is required. In the conventional optimization geometric or parameter optimization is common. In these methods, just the boundaries of the shape can be changed. In this study topology optimization as a powerful tool is used. It gives more freedom to the designer to gain higher performance and to approach more close to the consumer goals.In this work, a combinatorial optimization method based on a meta-heuristic algorithm combined with a local method based on a Local Importance Measure is offered to improve the results. The aim of this research is to seek for material distribution inside the electromagnetic actuator to have a lighter weight and the maximum possible force or torque. It is possible to extend this method to the different active parts of electrical actuators and machines satisfying different goals.
Created from Fastlane, Scopus look-up
Keywords: genetic algorithms; global optimization; hybrid algorithm; local optimization; metaheuristic algorithm; topology optimization

Practical Evaluation of a Passive Stator Cooling Concept without Thermal Stacking - Hahn, Ingo; Lindner, Andreas (IEEE, 2017)
UnivIS-Import:2017-07-10:Pub.2017.tech.IE.LEEAS.practi

Prediction of Voltage Stress to Ground at Synchronous Motor Terminals in Power Drive Systems - Fritsch, Christoph; Hahn, Ingo (2023 25th European Conference on Power Electronics and Applications (EPE'23 ECCE Europe), 2023)
This paper presents an easy to parameterize simulation method to predict the voltage stress to ground at synchronous motor terminals. The simulation allows to identify critical operation speeds with highest voltage stress in amplitude and frequency. Also, the voltage stress of planned drive trains can be predicted.
CRIS-Team Scopus Importer:2024-12-16
Keywords: insulation; partial discharge; synchronous motor; Three-phase motor drive

Resistance- and Inductance-Based Self-Sensing Control using Short-Circuited Windings on the Rotor of a SPMSM - Hittinger, Christoph; Hahn, Ingo (45th Annual Conference of the IEEE Industrial Electronics Society (IECON), 2019)
CRIS-Team WoS Importer:2020-05-15

Self-Sensing Control of Permanent-Magnet Synchronous Machines with Multiple Saliencies Using Pulse-Voltage-Injection - Chen, Lei; Götting, Gunther; Dietrich, Simon; Hahn, Ingo (IEEE, 2015)
This paper describes a self-sensing control scheme based on pulse-voltage-injection for permanent-magnet synchronous machines (PMSMs). Multiple saliencies, as well as the saturation and reluctance-based coupling effects are studied by means of analytical methods and are proved with FEM simulations and measurements. These phenomena cause a constant estimated error of the rotor angle as well as periodic errors with harmonics of order 6k. The primary saliency of the considered interior PMSM with concentrated windings (CWIPMSM) is strongly dependent on the load, so that the self-sensing capability disappears at some critical operating points. In this study, the parameters of the multiple saliencies are identified based on the proposed self-sensing method. The secondary saliencies are compensated with a closed loop control structure. The effectiveness of the proposed method is confirmed by experimental results.
UnivIS-Import:2016-06-01:Pub.2015.tech.IE.LEEAS.selfse
Keywords: High-Frequency Model; Multiple Saliencies; Permanent-Magnet Synchronous Machine; Pulse-Voltage-Injection; Self-Sensing

Sensorless Capability of an Interior Permanent Magnet Synchronous Machine with a Short-Circuited Rotor Winding - Hahn, Ingo; Graus, Johannes (IECON, 2014)
UnivIS-Import:2015-04-16:Pub.2014.tech.IE.LEEAS.sensor_7

Short-Circuited Rotor Windings for Improving the Electromagnetic Saliency for Inductance- and Resistance-Based Self-Sensing Control - Hittinger, Christoph; Hahn, Ingo (2019 IEEE 28th International Symposium on Industrial Electronics (ISIE), 2019)
Keywords: self-sensing control; resistance-based; inductance-based; short-circuited rotor windings; SPMSM

Simulation and optimization of a Flux-Switching machine with large air-gap using finite element method - Lindner, Andreas; Hahn, Ingo (PEMD 2014, 2014)
A 6/8 flux-switching machine with permanent magnets and a large air-gap (δ = 2.5mm) is optimized using finite element method. Maximum output torque and minimum torque ripple is achieved by means of alteration the C-shaped stator core dimensions and the rotor pole shape. Simulation results show, that the characteristics of the flux-switching machine are very suitable for applications where large air-gaps, high-speed operation and high rotor temperatures are requirements.
UnivIS-Import:2015-04-16:Pub.2014.tech.IE.LEEAS.simula
Keywords: C-core design; Flux-switching permanent magnet machine; Large air-gap

Simulation des Bahnspannungsverhaltens in bahnverarbeitenden Maschinen unter Berücksichtigung von Dehn- und Gleitschlupf - Göb, Mario; Hahn, Ingo (SPS/IPC/DRIVES, 2009)
UnivIS-Import:2015-04-16:Pub.2009.tech.IE.LEEAS.simula

Simulation of a permanent magnet flux-switching machine with reduced outer stator leakage flux - Lindner, Andreas; Hahn, Ingo (2014 International Symposium on Power Elektronics, Electrical Drives, Automation and Motion (SPEEDAM 2014), 2014)
A small size permanent magnet flux-switching machine is designed with the aim to reduce the undesired leakage flux outside the stator. Different design alternatives are considered using a C-core type permanent magnet flux-switching machine. The leakage flux outside the stator of a permanent magnet flux-switching machine can effectively be reduced by altering the stator structure. To preserve the high torque capability of the flux-switching machine different design modifications of the stator structure have to be applied. © 2014 IEEE.
UnivIS-Import:2015-04-16:Pub.2014.tech.IE.LEEAS.simula_46
Keywords: C-core; EMC; FSPM design; leakage flux; switched-flux machine

Simulation of a toroidal wound flux-switching permanent magnet machine - Lindner, Andreas; Hahn, Ingo (IECON 2014, 2014)
UnivIS-Import:2015-04-16:Pub.2014.tech.IE.LEEAS.simula_5

Structural Optimization of an Electromagnetic Actuator Based on Genetic Algorithm, Greedy Search and Their Combination - Ruzbehi, Shabnam; Hahn, Ingo (IEEE International Symposium on Industrial Electronics, 2019)
In the last years, optimal operation and usage of electrical machines leads to an increased attention for improving the operating behaviour and changes in the electrical machine's structure for industrial applications. In conventional optimization, it is common to use parametric design and geometric optimization, but this manuscript presents the structural or topological optimization. This method gives more freedom to the designers to adapt high performance electrical machines to the customer goals. The implementation of the proposed method for structural design and topology optimization is applied to the detailed design of an electromagnetic actuator.In general, electrical machinery is aimed to produce high torque and power at minimum weight to gain a high torque and power density. Therefore, high force or torque and low weight are the two main goals in this work for designing electrical machines, which can satisfy mechanical, structural and magnetic constraints. To show the validity and the opportunities of the proposed optimization method, the design of a simple magnetic actuator using a metaheuristic global optimization method (genetic algorithm (GA)) and a deterministic local search (greedy algorithm) is investigated at first and, secondly, a combination of both of these methods is presented for a highly nonlinear problem. The given design goals have been successfully achieved using the proposed structural optimization method to find the best suited topology.
CRIS-Team Scopus Importer:2019-08-23
Keywords: genetic algorithms; global optimization; greedy algorithm; local optimization; metaheuristic algorithm; topology optimization

Structural Optimization of PM Synchronous Machine Based on Multi-objective Algorithm for Lower Torque Ripple and Volume - Ruzbehi, Shabnam; Hahn, Ingo (2022 23rd International Conference on the Computation of Electromagnetic Fields, COMPUMAG 2022, 2022)
In this study, a Topology Optimization procedure of a 36kW permanent magnet synchronous motor (PMSM) is presented to minimize the weight, torque ripple and cogging torque, also to ensure the maximum average torque in a reasonable amount using a novel Evolutionary Algorithm. The structure of the rotor and magnets, which are effective in the performance and weight of PMSM are optimized together and compared with the conventional design. In order to show the validity of methodology performance, also to investigate electromagnetic and operational performances of the motor, the magnetic field is analyzed using finite element method with FEMM software in a discretized design area and online optimization process via Matlab. The results lead to better flux linkage and back-EMF wave shape, and torque ripple and cogging torque reduction, which cause acoustic noise and vibration improvement. This new Topology Optimization method can be extended to other active parts of the machine with different objective functions.
CRIS-Team Scopus Importer:2022-09-02
Keywords: Genetic algorithm; Permanent magnet synchronous machine; Topology optimization; Torque

Subdomain Modeling of a Flux Switching Machine with Buried Permanent Magnets - Sisterhenn, Philipp; Hahn, Ingo (2024 Energy Conversion Congress and Expo Europe, ECCE Europe 2024, 2024)
Keywords: buried magnets; FSM; flux switching machine; subdomain model; SDM

Thermal Investigation and Enhancement of Advanced Cooling Techniques for a Large Air-Gap Flux-Switching Permanent Magnet Machine. - Hahn, Ingo; Lindner, Andreas (IEEE, 2017)
UnivIS-Import:2017-07-10:Pub.2017.tech.IE.LEEAS.therma

Topology optimization of a nonlinear electromagnetic actuator based on a local importance measure - Ruzbehi, Shabnam; Hahn, Ingo (Proceedings - 2019 IEEE Workshop on Electrical Machines Design, Control and Diagnosis, WEMDCD 2019, 2019)
Optimal usage of electrical machines lead recently to an increased attention to have machines with improved operating behaviour and changes in the mechanical structure of these machines. In this study, a topological optimization technique based on local gradients is applied to a magnetic actuator, replacing the conventional methods, which are called geometric or parametric optimization. This new method gives more freedom to the designers, in order to gain high performance electrical machines according to the customer's goals. The design space is discontinuous and consists of simple square cells. In this new method, the more important cells with respect to some optimization criteria will determine the optimal topology. The goal is to seek for material distributions that reduce the weight while preserving the magnetic force or torque at a specific level. To show the validity of this method, at first, this method will be applied to a problem with two types of materials (air and iron). Afterwards it will be extended to three types of materials (air, iron and copper), which extremely improves the objective function's value. The gained results verify the validity of the improved method. The results in this case study indicate that this method operates well. Furthermore, it is shown that the proposed method can be extended to gain new shapes of the different active parts of a motor or a transformer to finally reach optimal designs of electromagnetic devices.
CRIS-Team Scopus Importer:2019-11-26
Keywords: Design optimization; Global optimization; Sensitivity; Topology optimization

Topology optimization of a PMSM based on a local method to gain lightweight structure and better operation - Ruzbehi, Shabnam; Hahn, Ingo (11th International Conference on Power Electronics, Machines and Drives (PEMD 2022), 2022)
In this study, a Topology Optimization procedure has been applied to a 3-phase permanent magnet synchronous machine (PMSM) to gain a lighter weight motor with lower torque ripple and cogging torque, while the average torque maintains at a reasonable level with a novel local method, named Local Importance Measure (LIM). The validity of this method is checked with an electrical machine's permanent magnet and rotor part to reduce production costs, permanent magnet and material consumption, and reach a better motor performance. To give more freedom to the designers, replacing the conventional parameter optimization, topology optimization is used. To overcome continuous grey optimization with intermediate material characteristics, a discretized binary method is applied. The electromagnetic field is calculated by using the 2D finite element software FEMM, and the optimization is processed via Matlab. The results verified the method's validity in reaching to a machine design with lower torque ripple and cogging torque, which causes less vibration and acoustic noise. In addition, an improvement in the flux linkage and back-EMF waveform is gained. It is shown that the proposed method can be extended to different kinds of electromagnetic devices, with different objective functions.
Keywords: TOPOLOGY OPTIMIZATION; PMSM; BACK-EMF; TORQUE; COGGING TORQUE.

Topology Optimization of a PM Synchronous Machine Based on Novel Metaheuristic Algorithm for Lower Cogging Torque and Magnet Volume - Ruzbehi, Shabnam; Hahn, Ingo (Proceedings of the IEEE International Conference on Industrial Technology, 2022)
This paper proposes the Topology Optimization procedure of a three-phase permanent magnet synchronous motor (PMSM) to minimize weight, torque ripple and cogging torque, while preserving the average torque using a Binary Evolutionary Algorithm. To show the validity of the proposed topology optimization method, the design of the electrical machine's permanent magnet part is performed to enhance the merits of PMSM, with reduced production costs, lower permanent magnet consumption and improved motor performance. The magnetic field is calculated using the 2D finite element software FEMM in a discretized design area. The optimization process is done via MATLAB. The results show an improvement in the flux linkage and back-EMF waveform. Also, torque ripple and cogging torque reduction lead to less vibration and acoustic noise. The proposed topology optimization method can be extended to other active parts of the machine with different objective functions.
CRIS-Team Scopus Importer:2024-12-16
Keywords: Back-EMF; Cogging torque; Genetic algorithms; PMSM; Topology optimization; Torque

Topology Optimization with Improved Genetic Algorithm of an Electromagnetic Actuator - Ruzbehi, Shabnam; Hahn, Ingo (2019 22ND INTERNATIONAL CONFERENCE ON THE COMPUTATION OF ELECTROMAGNETIC FIELDS (COMPUMAG 2019), 2019)
CRIS-Team WoS Importer:2020-09-04

Torque Harmonics Minimization of Double-Stage Magnetic Gear Transmission System - Floris, Andrea; Serpi, Alessandro; Damiano, Alfonso; Hahn, Ingo (45th Annual Conference of the IEEE Industrial Electronics Society (IECON), 2019)
CRIS-Team WoS Importer:2020-05-15

Two-level Topology Optimization based on a Metaheuristic Method and Morphological Reconstruction - Ruzbehi, Shabnam; Hahn, Ingo (IECON 2021 – 47th Annual Conference of the IEEE Industrial Electronics Society, 2021)
This paper offers a Topology Optimization (TO) method to replace conventional parameter optimization, which is a common method for electrical machine’s or electromagnetic device’s design optimization. In most of the final designs gained with TO, there are challenges in the manufacturing process using the nowadays available manufacturing technologies. Therefore, this work investigated the approach on two tasks, in the first level a global optimization method, called Enhanced Binary Genetic Algorithm is applied to the design domain. After optimization with this meta-heuristic method, some holes inside the structure or some spread iron cells appear. This drawback will be improved in the second level by one of the image processing methods, called Morphological Reconstruction, to gain a smoother shape to reduce the manufacturing complexities while reaching reasonable technical characteristics. The goal is to find a lighter weight of the structure while preserving the force in a suited amount. The proposed method is applied to an E-core actuator as a case study. After using the proposed hybrid optimization method, air cells appear around some parts of the actuator’s coil, which are used to extend the copper areas, so that the magnetic force considerably increases. In general, it is possible to extend the method to different active parts of the electrical machines.<br
Keywords: Morphological Reconstruction; Binary Genetic; Algorithm; topology optimization; Actuators

Two-level topology optimization of an electromagnetic actuator based on genetic algorithm and neighbourhood method - Ruzbehi, Shabnam; Hahn, Ingo (Proceedings of the IEEE International Conference on Industrial Technology, 2020)
In this paper a multi-objective topology optimization method is presented to find an innovative design and to improve the conventional iron core structures, which are used in rotary electrical machines and electromagnetic devices. The goals are to find an optimal material distribution with less material usage, which makes the device lighter, and also considering the magnetic force to remain in a reasonable range. At first, a meta-heuristic method, called Enhanced Binary Genetic Algorithm (EBGA) is used to gain an optimal material distribution. In the next step, as a post-processing task, a Neighborhood method is used to improve the technical results, to remove the voids inside the iron shape and to make the structure more suitable for the manufacturing process according to the nowadays available manufacturing technologies. This method is inspired by the image processing technique. Afterwards, a third type of material (copper) is added to the design domain. Air cells, which surround some parts of the copper coil area, will be replaced by copper. With these three steps the amount of force increases significantly, while a lighter optimal shape is obtained. As a case study, the proposed method is tested on a simple electromagnetic nonlinear actuator. The results of this work show that it is possible to extend the method to different active parts of electrical machines such as permanent magnet, stator and rotor.
CRIS-Team Scopus Importer:2020-05-12
Keywords: Genetic algorithm; Magnetic actuator; Multi-level optimization; Neighborhood method; Topology optimization

Utilisation of magnetic saliency for sensorless-control of permanent-magnet synchronous motors - Reill, Josef; Piepenbreier, Bernhard; Hahn, Ingo (SPEEDAM 2010, 2010)
This paper presents a new method for sensorless control of permanent magnet synchronous machines (PSM) in low speed and standstill region. Actually, there exist many solutions for speed controlled applications via interpretation of the voltage equations of the PSM. There are some well known algorithms to handle sensorless operation up to standstill, too. Most of these methods use a high frequency signal and some kind of filter technique for demodulation. In this paper a new frequency domain based algorithm is proposed. The main advantage of the new strategy is the precise separation of the fundamental wave and hf-signal and avoidance of conventional filters. For phaselag reasons all filter techniques suffer from the demand for high sampling rates. The presented algorithm is compared with known methods by far better applicable to conventional industry power-converters that often have switching frequencies limited to 8 kHz. © 2010 IEEE.
UnivIS-Import:2015-04-16:Pub.2010.tech.IE.LEEAS.utilis
Keywords: Sensorless control; Signal injection; Vector control